First In Situ Observations of Gaseous Volcanic Plume Electrification. Issue 6 (25th March 2019) - Nicoll, Keri; Airey, Martin; Cimarelli, Corrado; Bennett, Alec; Harrison, Giles; Gaudin, Damien; Aplin, Karen; Koh, Kuang Liang; Knuever, Marco; Marlton, Graeme
Abstract: Volcanic plumes become electrically charged, often producing spectacular displays of lightning. Previous research has focused on understanding volcanic lightning, primarily the large electric fields produced by charging of ash particles. Here we report on the previously overlooked phenomenon of volcanic plume electrification in the absence of detectable ash. We present the first in situ vertical profile measurements of charge, thermodynamic, and microphysical properties inside predominantly gaseous plumes directly above an erupting volcano. Our measurements demonstrate that substantial charge (at least ±8, 000 pC/m 3 ) is present in gaseous volcanic clouds without detectable ash. We suggest that plume charging may be enhanced by the emission of radon gas from the volcano, which causes ionization. This presents a hitherto unrecognized, but likely to be common, mechanism for charge generation in volcanic plumes, which is expected to modulate plume characteristics and lifetime. This process is currently neglected in recognized mechanisms of volcanic plume electrification. Key Points: We present the first in situ profiles of thermodynamic, microphysical, and charge properties in a gaseous volcanic plume above an erupting volcano Gaseous plumes with no detectable ash are, unexpectedly, significantly charged (up to ±8, 000 pC/m 3 ) A new mechanism for plume electrification related to radon emission from volcanic vents is proposed to explain the charge observations